2020
DOI: 10.1111/ejh.13533
|View full text |Cite
|
Sign up to set email alerts
|

Association of anticoagulation dose and survival in hospitalized COVID‐19 patients: A retrospective propensity score‐weighted analysis

Abstract: Background Hypercoagulability may contribute to COVID‐19 pathogenicity. The role of anticoagulation (AC) at therapeutic (tAC) or prophylactic doses (pAC) is unclear. Objectives We evaluated the impact on survival of different AC doses in COVID‐19 patients. Methods Retrospective, multi‐center cohort study of consecutive COVID‐19 patients hospitalized between March 13 and May 5, 2020. Results A total of 3480 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(115 citation statements)
references
References 20 publications
2
102
3
2
Order By: Relevance
“…Data were censored at 35 days of follow up in n=430 (10.0%) patients with a follow up longer than 35 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were censored at 35 days of follow up in n=430 (10.0%) patients with a follow up longer than 35 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pesavento et al (34) showed in a smaller cohort of Italian patients that the rate of relevant bleeding was higher in patients treated with (sub)therapeutic doses of anticoagulants, while overall mortality tended to be higher as compared to patients treated with standard prophylactic doses. Other observational studies reported that treatment with a therapeutic/higher dosage of anti-coagulant drugs was associated with a higher incidence of bleeding, despite a decrease of in-hospital mortality (7,35). HIT is a severe immune-mediated complication of heparin therapy, leading to platelet activation, platelet consumption, and thrombin generation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Because of the high risk of thromboembolic complications and heparin's unique pharmacology demonstrating a reduction in both inflammation and coagulation markers in COVID-19, heparins are being studied for additional clinical endpoints of reduction in hospitalizations, progression to non-invasive mechanical ventilation, as well as mortality. Some, but not all, recently reported retrospective cohort studies, suggest an in-hospital mortality benefit for both UFH and LMWH administered at both prophylaxis and therapeutic treatment doses, especially in patients with more severe COVID-19 as evidenced by elevated D-dimer or need for mechanical ventilation [ 76 , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] ] (Summarized in Table 2 ).…”
Section: Clinical Trials Of Heparins For Prophylaxis Of Venous Thrombmentioning
confidence: 99%
“…In the few studies that have reported the frequency of major bleeding, results are mixed with two studies reporting no difference in major bleeding between therapeutic anticoagulation and prophylactic anticoagulation and one study reporting an increased risk of major bleeding [ 96 , 98 , 99 , 101 ]. Because the data reported in these studies are limited with some lacking details regarding heparin type, dose, the reason treatment versus prophylaxis dosing was selected, as well as the potential for confounding, randomized prospective trials are needed.…”
Section: Clinical Trials Of Heparins For Prophylaxis Of Venous Thrombmentioning
confidence: 99%
“…Less advanced disease stages, a lower number of patients with severe aRF at admission and an increased proportion of patients treated with anticoagulant therapy may have thus contributed to decreased mortality [ 14 , 15 ]. In fact, PaO2/FiO2<200 mmHg [ 10 ] and D-dimer >2.000 FEU [ 12 ] were demonstrated to be independent risk factors for adverse outcomes, while the increased use of systemic corticosteroids [ 6 , 7 , 14 ] and anticoagulation [ 13 , 14 ] showed a reduction in mortality in patients with severe COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%